The Effect of Organizing Learning Activities Based on Gamification Concept toward Problem Solving Skills of Nursing Students - Prajankett, Ong-on; Chamnongchit, Sirirat; Sanee, Aree; Charoensan, Pornnapa (Journal of The Royal Thai Army Nurses, 2021)
This quasi-experimental research applied the gamification concept in education. The concept is the integration of gaming with learning technology. Leading to classroom engagement and practice of problem-solving skills from situations in the game. Therefore, we are interested in using the game “Solve the outbreak” to organize learning activities based on the concept of gamification. So that the learner was an epidemic investigator in various epidemic situations. The aims of this research were to 1) analyze and compare the problem-solving skills of nursing students before and after providing the learning activities with the gamification approach and 2) study the students’ opinions towards the learning activities with the gamification approach. One group, pretest-posttest design was carried out on a sample of 63 second-year nursing students. The samples planned themselves to play “Solve the outbreak” game effectively within 4 weeks. The research instruments were the problem-solving skills test and the opinion survey. Reliability test using the Kuder-Richardson 20 are 0.82. The data were analyzed by using descriptive statistics and paired t-test. The results found that problem-solving skills increased after participating in the learning activities based on the concept of gamification with statistically significant at .05 level. Student’s opinions show that they learned about diseases and outbreaks management in an enjoyable and engaging way. The scenarios stimulated their problem-solving thinking to save lives.